The Effect of Descriptive Norms, Injunctive Norms, and Enjoyment-based Motivation on Buying Behavior of Fashion Goods: A Case Study of MSMEs in Jambi City - Usmayanti, Vivi; Fahdillah, Yosi; Pangestu, Mira Gustiana; Prasasti, Laura; Suratno, Eddy; Kartika, Yulia Dwi (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
Fashion trends, especially for young people, are an inseparable lifestyle. Satisfaction in following trends is one of the factors that encourages young people to always follow trends. Besides that, there are limitations to social norms that become limitations in exploring fashion trends. This study examines enjoyment-based motivation, descriptive norms, and injunctive norms on the fashion buying behavior of young SMEs in Jambi province. A total of 303 participants filled out online questionnaires, and the data collection period was three months (February-April, 2023. Data analysis used the PLS-SEM test. The results of this study indicate that enjoyment-based motivation, descriptive norms and injunctive norms have a positive effect on buying behavior This research contributes to determining the personal factors of the customer and social norms in determining the purchase of fashion products, so that MSME actors can consider both social products with social norms and quality improvement to fulfill the enjoyment based motivation of customers in the long term.